Identification of Burkholderia pseudomallei Mimotope using Phage display approach - Chua, K.H.; Chai, H.C.; Puthucheary, S.D. (2008)
This study reportsa sequential biopanning against serum obtained from a patient infected with B. pseudomallei using a phage display peptide library. A peptide bearing the consensus sequence NKNSFDAWLQSF was obtained after 3 rounds of biopanning and it partly resembles the sequence 35FDAWLAAQEF44 of B. pseudomallei site-specific recombinase, which is a phage integrase family protein. Overall, the mimotope obtained in this study could be a potential candidate for the development of a cost effective diagnostic test or vaccine in the future.